The Effect of Inflation, Government Expenditure, Population, and Wages on Poverty in Sumatra Island 2017-2021 - Ai Cahyani; Antoni Sitorus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Poverty indicates a population's inability to meet average minimum needs. This study aims to analyze the impact of inflation, government spending, population, and wages on poverty in Sumatra Island. This observation is quantitative research and auxiliary data in the form of time series data using panel data from 2017 to 2021 in as many as ten provinces with panel data analysis, which is assisted by the Eviews 12 application. Based on the panel results, it is concluded that the variables of inflation, government spending, and wages significantly positively affect poverty in Sumatra. In contrast, population has no impact on poverty in Sumatra.